Sistem Pendidikan Suku Asli Melayu Kecamatan Bantan - Muhajir Darwis; Wan Muhammad Fariq; Saim (STAIN Bengkalis, 2022)
This research is motivated by the fact that the Indigenous Malay people living in Bantan District can be considered isolated, remote, and inland, with limited access to educational facilities provided by the government. The Indigenous Malay people have become complacent with their current conditions and situation. The aim of this research is to determine the level of educational awareness among the Indigenous Malay people in Bantan District, Bengkalis Regency, and the factors contributing to their educational backwardness. Additionally, the research seeks to identify an appropriate educational concept to change the Indigenous Malay people's paradigm regarding the importance of education for their well-being. The method used in this research is qualitative research. The data collection techniques include interviews, observation, and documentation. The results show that educational participation among the indigenous community in Bantan District for primary education is relatively significant, reaching 80 percent of the total school-age children. For junior high school education, participation is also quite high at 65 percent. However, the participation rate for high school education is relatively low, at only 45 percent. Although primary education participation is generally good, there is still a significant dropout rate, with children often leaving school when they reach the third or fourth grade. Factors contributing to the educational backwardness of the Indigenous Malay people in Bantan District include peer influence from those not attending school, weak economy, low motivation, lack of parental encouragement, low self-confidence, and insufficient educational infrastructure. The educational concept proposed for the Indigenous Malay community in Bantan District is the Indigenous Education Concept. The indigenous learning system is a system used by traditional communities to maintain and preserve their social systems for their survival.